Advances in direct transesterification of algal oils from wet biomass. (May 2015) - Park, Ji-Yeon; Park, Min S.; Lee, Young-Chul; Yang, Ji-Won
Highlights: Recent developments in wet oil extraction and biodiesel conversion from microalgae. Direct transesterification omitting a separate oil extraction step for wet microalgae. Needs for purification of microalgal oils and upgrading of biodiesel properties. Abstract: An interest in biodiesel as an alternative fuel for diesel engines has been increasing because of the issue of petroleum depletion and environmental concerns related to massive carbon dioxide emissions. Researchers are strongly driven to pursue the next generation of vegetable oil-based biodiesel. Oleaginous microalgae are considered to be a promising alternative oil source. To commercialize microalgal biodiesel, cost reductions in oil extraction and downstream biodiesel conversion are stressed. Herein, starting from an investigation of oil extraction from wet microalgae, a review is conducted of transesterification using enzymes, homogeneous and heterogeneous catalysts, and yield enhancement by ultrasound, microwave, and supercritical process. In particular, there is a focus on direct transesterification as a simple and energy efficient process that omits a separate oil extraction step and utilizes wet microalgal biomass; however, it is still necessary to consider issues such as the purification of microalgal oils and upgrading of biodiesel properties.